The voodoo doll task: Introducing and validating a novel method for studying aggressive inclinations. Issue 6 (22nd July 2013) - DeWall, C. Nathan; Finkel, Eli J.; Lambert, Nathaniel M.; Slotter, Erica B.; Bodenhausen, Galen V.; Pond, Richard S.; Renzetti, Claire M.; Fincham, Frank D.
Abstract Aggression pervades modern life. To understand the root causes of aggression, researchers have developed several methods to assess aggressive inclinations. The current article introduces a new behavioral method—the voodoo doll task (VDT)—that offers a reliable and valid trait and state measure of aggressive inclinations across settings and relationship contexts. Drawing on theory and research on the law of similarity and magical beliefs (Rozin, Millman, & Nemeroff [1986], Journal of Personality and Social Psychology, 50, 703−712), we propose that people transfer characteristics of a person onto a voodoo doll representing that person. As a result, causing harm to a voodoo doll by stabbing it with pins may have important psychological similarities to causing actual harm to the person the voodoo doll represents. Nine methodologically diverse studies (total N = 1, 376) showed that the VDT had strong reliability, construct validity, and convergent validity. Discussion centers on the importance of magical beliefs in understanding the causes of aggressive inclinations. Aggr. Behav. 39:419–439, 2013. © 2013 Wiley Periodicals, Inc.